Exposure to styrene. Uptake, distribution, metabolism and elimination in man. - Wigaeus, Ewa; Lof, A; Bjurström, Rasmus; Nordqvist, M B (Scandinavian Journal of Work, Environment & Health, 1983)
Exposure to styrene: Uptake, distribution, metabolism and elimination in man. Scand j work environ health 9 (1983) 479-488. Eight male subjects were exposed for 2 h to about 2.88 mmol/m3 (300 mg/m3) of styrene vapor during light physical exercise. The uptake of styrene averaged 4.4 mmol, or 68% of the amount supplied. The arterial blood concentration of styrene reached a relatively stable level of about 20 mumol/l after 75 min of exposure. The calculated value of blood clearance was 1.7 (SD 0.3) l/min, and the extraction ratio about 0.2. The half-time for the elimination phase was 41 (SD 7) min, and the calculated volume of distribution 99 (SD 13) l. The concentration of styrene in the subcutaneous adipose tissue was about 50 mumol/kg 30-90 min after exposure. The concentration of nonconjugated styrene glycol in blood increased linearly during exposure and was about 15% of the styrene concentration in blood at the end of exposure. It was eliminated with a half-time of 72 (SD 13) min. Within 28 h after exposure 58% of the total uptake of styrene was recovered in the urine as mandelic and phenylglyoxylic acid. Their excretion half-times (0-20 h) were 3.6 (SD 0.4) and 8.8 (SD 1.3) h, respectively. Styrene-7,8-oxide was detected and quantified in blood in a complementary study.